Eu Black Campaign 2017: Global Palm Oil Price Surge Vs. Indonesia's Export Resilience To Asia-Europe Markets - Djono Albar Burhan; Lufita Nur Alfiah; Zawil Hijri; Lely Yuliani; Dewi Susanti (Jurnal Mamangan, 2024)
The European Parliament's 2017 resolution on palm oil and rainforest deforestation, framed as a black campaign, significantly depressed global palm oil prices but showed no substantial impact on Indonesian palm oil exports to the Netherlands, Spain, China, and India. Employing an event study methodology with paired sample t-tests on monthly data (August 2024–October 2025), this research reveals a mean price drop from USD 790.08 to USD 741.49 per metric ton (p=0.004), while export values remained statistically unchanged across markets (p>0.05). Findings underscore market resilience in non-EU importers and suggest policy needs for sustainability certification amid ongoing trade tensions